Wheat (Triticum aestivum) Adaptation to Lombok Island Indonesia - Akhmad Zubaidi; Mansur Ma'shum; Gurjeet Gill; Glenn K. McDonald (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Wheat is a temperate crop; therefore, effort is needed in adapting it to tropical areas. Lombok Island is suggested to be a potential wheat growing area. To investigate the feasibility of wheat production on Lombok and the adaptation of wheat to the current cropping systems, field experiments were carried out at six sowing times in 2010 and three sowing times in 2011 at three different sites up to 1000 meters above sea level (m asl) to represent low, medium and high elevation areas. Eight Australian and two Indonesian wheat varieties were selected to represent a range in maturity types. Six sowing dates in 2010 were arranged two weeks apart, from 19 April to 27 June, and three sowing time in 2011 were from 20 May to 19 June. Plant development was rapid at this continuously high temperature environment with flowering occurring 40-70 days after sowing (DAS). Wheat productivity was influenced by elevation and sowing date, at lowland, yields were about 1 t ha-1 or less, whereas at 500 m asl and above ranged from 2-3 t ha-1. Mid-season varieties were higher yielding than earlier or later flowering varieties. The optimum sowing time was from mid-May to early-June.